Merkel cell tumour of the eyelid and reconstruction with the Cutler-Beard technique: a clinicopathologic case report - (:unkn) unknown (My University, 1994)
A case of Merkel cell tumour that developed on the left upper lid of a 76-year-old white man is reported. The diagnosis was ultrastructurally made by demonstrating characteristic light microscopic features of Merkel cell carcinoma; such as large, round nuclei and frequent mitoses. Immunohistochemically, the tumour cells were shown to possess simple epithelia-type keratin intermediate filaments. Merkel cell tumour probably develops from precursor cells which give rise to keratinocytes and Merkel cells, and nearly one out of 10 Merkel cell tumours occur in the eyelid and periocular region. They tend to be bulging lesions near the lid margin of elderly patients. The condition can be misdiagnosed as lymphoma, oat cell carcinoma, malignant melanoma, sweat gland tumours, neuroblastoma and Ewing's sarcoma, and frequently invades lymphatic vessels. Nearly one out of three Merkel cell tumours recur and two thirds cause regional lymph node metastases. Wide surgical resection and reconstructive procedures, should be followed by routine postoperative irradiation. This patient was treated with wide resection and the Cutler-Beard technique, then scheduled for radiotherapy.
Keywords: Humans; Aged; Male; Combined Modality Therapy; Surgery, Plastic; Skin Neoplasms; Carcinoma, Merkel Cell; Eyelid Neoplasms